The ball SITE sign: Ball sports-induced targetoid erythema in a racquetball player - Cohen, Philip R. (Dermatol Pract Concept, 2015)
BACKGROUND: Cutaneous injury following impact of a high velocity ball to the skin may result in either erythema or purpura or both. The lesion typically appears as an annular ring of erythema with or without accompanying ecchymosis when the skin is contacted by a paintball, a ping pong ball, a racquetball or a squash ball. PURPOSE: To describe a girl with targetoid erythema following impact of a racquetball on her flank and back and to review other sports associated with this response to skin injury. METHODS: PubMed was used to search the following terms, separately and in combination: ball, erythema, paint, ping pong, purpura, racquetball, sign, site, sports, squash, targetoid. All papers were reviewed and relevant manuscripts, along with their reference citations, were evaluated. RESULTS: A 13-year-old girl developed an annular red ring surrounding a central area of normal appearing skin on her right flank and upper back where a racquetball traveling at a high velocity contacted her skin. Similar appearing lesions of targetoid erythema have been described at the cutaneous impact sites of either paintballs, ping pong balls, squash balls; in addition to erythema, purpura may also concurrently appear or subsequently develop at the contact location of the ball with the skin. CONCLUSIONS: Targetoid erythema is a pathognomonic cutaneous presentation resulting from the impact of either a paintball, ping pong ball, racquetball or squash ball—that is traveling at a high velocity—with a sport participant’s skin. The ball SITE (sports-induced targetoid erythema) sign is suggested as a unifying nomenclature to designate this unique, ball sport-associated, cutaneous dermatosis in athletes participating in sports in which high velocity impact of the ball with the skin may occur.